If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -45 + X = -27 Solving -45 + X = -27 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + X = -27 + 45 Combine like terms: -45 + 45 = 0 0 + X = -27 + 45 X = -27 + 45 Combine like terms: -27 + 45 = 18 X = 18 Simplifying X = 18
| -13=k-13+14k | | 5m-5=-25 | | x-.20x=338 | | 10x+40=4x+8 | | 45+X=-27 | | 8+10k-11k=0 | | x-.20x=512 | | (-30(-17))-(210(-3))= | | -36=-11n+8n | | 6y-60=42 | | 12=x-(-11) | | -36=k-13+14k | | 13p+6=32 | | sin^-1(3.2/4) | | 34=x+9+12 | | 11m+8=19 | | 0.3x-0.6=0.2x+7 | | -n-7=-16 | | 0=-13b+13b | | 9y^4+12y^2+1=0 | | -13z+13=26 | | -3(4n+6)=-6(n-8) | | .03x+.05(200-x)=9 | | 7m-25=-4 | | 2m+20=26 | | X^2-8x-4=-11 | | 3.3=1.5-0.4 | | x+4k=0 | | -18=x-5 | | -15x+25=-95 | | 9z-17=-35 | | 10y-2=48 |